Ortaöğretim öğrencilerinin rutin olmayan matematik problemi çözme başarılarının matematik problemi çözmeye yönelik inançları bağlamında incelenmesi - Elmas, Özlem (My University, 2023)
Bu çalışmada; ortaöğretim öğrencilerinin rutin olmayan matematik problemi çözme başarılarının matematik problemi çözmeye yönelik inançları bağlamında incelenmesi amaçlanmıştır. Araştırmada nitel yaklaşıma dair durum çalışması deseni kullanılmıştır. Araştırma grubu, kolay ulaşılabilir örneklemeyle oluşturulmuş olup, matematik problemi çözmeye yönelik inanç ölçeği öğrencilere uygulanarak, inanç ölçeği puanı düşük, orta ve yüksek seviyede altı öğrenci belirlenmiştir. Seçilen öğrencilere, hazırlanan 10 tane açık uçlu sorudan oluşan rutin olmayan problem testi uygulanmıştır. Veri toplama araçları olarak; uzman görüşleri ile hazırlanmış görüşme formu, rutin olmayan problem etkinlik gözlem formları ve ses kayıtları ile öğrencinin rutin olmayan problemleri çözdüğü dokümanlar kullanılmıştır. Toplanan nitel verilerin analizi betimsel olarak yapılmıştır. Araştırmanın sonucunda, öğrencilerin matematik becerileri, problemi anlamaya yönelik inançları ve problem çözme becerisine yönelik inançları arttıkça yani genel olarak matematik problemi çözmeye yönelik inanç düzeyleri arttıkça rutin olmayan problemleri çözme başarılarının da arttığı görülmüştür. Ulaşılan sonuçlar yorumlanıp tartışılmış, son olarak araştırmacı ve uygulayıcılara öneriler sunulmuştur.

In this study; it was aimed to examine the non-routine mathematics problem solving success of secondary school students on the context of their beliefs towards mathematical problem solving. The qualitative approach’s case study pattern was used in the research. The research group was formed with easily accessible sampling, and six students with low, medium, and high belief scale scores were determined by applying the belief scale for solving mathematical problems to the students. A non-routine problem test consisting of 10 open-ended questions was applied to the selected students. As data collection tools; Interview form prepared with expert opinions, non-routine problem activity observation forms, audio recordings, and documents in which the student solved non-routine problems were used. The analysis of the collected qualitative data was done descriptively. As a result of the research, it was observed that as students' mathematical skills, beliefs about understanding the problem, and beliefs about problem solving skills increased, that is, as their level of belief towars solving mathematical problems in general increased, their achievement in solving non-routine problems also increased. The results were interpreted and discussed, and suggestions were presented to researchers and practitioners.
Vestigation of the secondary school students’ non routine mathematical problem solving achievement on the context of beliefs towards mathematical problem solving
Keywords: Beliefs towards mathematical problem solving; Matematik; Matematik problemi çözme; Matematik problemi çözmeye yönelik inanç Mathematical problem solving; Mathematics; Non-Routine problem; Öğrenim ve öğretim; Problemler, alıştırmalar, vb; Problems, exercises, etc; Rutin olmayan problem; Study and teaching